Pertanggungjawaban Hukum Pengemudi Bus Angkutan Umum terhadap Kecelakaan yang Mengakibatkan Penumpang Meninggal Dunia: Analisis Yuridis di Polres Aceh Utara - Tengku Sulaiman; Irwansyah Nasution (Albayan Journal of Islam and Muslim Societies, 2024)
This study analyzes the legal accountability of public bus drivers involved in traffic accidents causing passengers' death, focusing on the criminal, civil, and administrative dimensions of responsibility. Using a normative-empirical juridical approach, the research examines statutory regulations, police investigation procedures, and court decisions related to fatal road accidents. The findings indicate that although the drivers’ negligence is the primary cause, systemic factors such as vehicle unfitness, weak supervision, and lack of passenger protection contribute significantly. Therefore, effective enforcement requires harmonizing criminal law principles with preventive transportation safety policies and the ethical responsibility of public transport operators.